2017
DOI: 10.1167/iovs.16-21204
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor 2 (FGFR2) Is Required for Meibomian Gland Homeostasis in the Adult Mouse

Abstract: PurposeLittle is known about the signaling mechanisms controlling meibomian gland (MG) homeostasis and the pathogenic processes leading to MG atrophy and dysfunction in dry eye disease (DED). We investigated the role of fibroblast growth factor receptor 2 (FGFR2) in the MG homeostasis of adult mice.MethodsA triple transgenic mouse strain (Krt14-rtTA; tetO-Cre; Fgfr2flox/flox), referred to as Fgfr2CKO mice, was generated in which the Fgfr2 gene is ablated by Cre recombinase in keratin 14 (Krt14)-expressing epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…An in vivo mouse genetic study showed that conditional gene deletion of Fgfr2b, an FGF receptor 2 (FGR2) isoform, in epidermal cells causes striking abnormalities in hair and sebaceous glands without affecting animal survival [103]. Reneker and colleagues [104] used a triple transgenic mouse strain (Krt14-rtTA; tetO-Cre; Fgfr2 flox/flox ), referred to as Fgfr2 CKO mice, to study the role of FGFR2 in Meibomian gland homeostasis. After a 2-week induction period, these mice developed severe Meibomian gland atrophy associated with reduced lipid (meibum) production (Oil-red-O staining), as well as evaporative DED symptoms related to MGD in human subjects [42,79].…”
Section: Fgfr2 Signaling In Meibomian Gland Homeostasis and Potentialmentioning
confidence: 99%
“…An in vivo mouse genetic study showed that conditional gene deletion of Fgfr2b, an FGF receptor 2 (FGR2) isoform, in epidermal cells causes striking abnormalities in hair and sebaceous glands without affecting animal survival [103]. Reneker and colleagues [104] used a triple transgenic mouse strain (Krt14-rtTA; tetO-Cre; Fgfr2 flox/flox ), referred to as Fgfr2 CKO mice, to study the role of FGFR2 in Meibomian gland homeostasis. After a 2-week induction period, these mice developed severe Meibomian gland atrophy associated with reduced lipid (meibum) production (Oil-red-O staining), as well as evaporative DED symptoms related to MGD in human subjects [42,79].…”
Section: Fgfr2 Signaling In Meibomian Gland Homeostasis and Potentialmentioning
confidence: 99%
“…Downloaded from proliferation and renewal. 20 Nevertheless, the significance of FGFR2 and its ligands in human MG homeostasis awaits further investigations. In summary, while our study is limited by the small sample size due to the poor availability of donor eyelids, the histopathological and biomarker analyses of MG tissues from a young donor with normal-appearing MGs, a young donor with ductal obstruction and two donors in their early 60s shed insights into the diverse underlying pathogenic mechanisms of MGD.…”
Section: Discussionmentioning
confidence: 99%
“…Using an inducible conditional knockout mouse model, we have demonstrated that FGFR2 signalling plays an essential role in MG acinar proliferation and renewal. 20 Nevertheless, the significance of FGFR2 and its ligands in human MG homeostasis awaits further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations